Cutaneous Manifestations of Familial Transthyretin Amyloid Polyneuropathy. (October 2016) - Lanoue, Julien; Wei, Nancy; Gorevic, Peter; Phelps, Robert G.
Abstract : Abstract: Familial amyloid polyneuropathy (FAP) is a rare inherited autosomal dominant form of systemic amyloidosis, which classically presents with severe motor, sensory, and autonomic dysfunction. Cutaneous involvement does not become clinically apparent until late stage symptomatic disease and is rarely reported in modern literature. Here, the authors review the clinical and histologic cutaneous findings of FAP previously described in the literature and report on 3 patients with unique genetic mutations (Thr60Ala and Gly6Ser; Trp41Leu; Glu89Gln) for which cutaneous involvement has not previously been described. Histologically, our patients showed variable amyloid deposition in the subcutaneous adipose tissue, papillary dermis, and dermal blood vessel walls. A review of the literature suggests cutaneous transthyretin deposition is an underrecognized feature of FAP that occurs early on in disease, even before neural involvement and related symptoms as seen in one of our patients. As such, a cutaneous punch biopsy can serve as quick, easy, and relatively noninvasive diagnostic tool in suspected cases.